Requirements Engineering Challenges in Large-Scale Agile System Development - Kasauli, Rashidah; Liebel, Grischa; Knauss, Eric; Gopakumar, Swathi; Kanagwa, Benjamin (IEEE., 2017)
Motivated by their success in software development, companies implement agile methods and their practices increasingly for software-intense, large products, such as cars, telecommunication infrastructure, and embedded systems. Such systems are usually subject to safety and regulative concerns as well as different development cycles of hardware and software. Consequently, requirements engineering involves upfront and detailed analysis, which can be at odds with agile (software) development. In this paper, we present results from a multiple case study with two car manufacturers, a telecommunications company, and a technology company that are on the journey to introduce organization wide continuous integration and continuous delivery to customers. Based on 20 qualitative interviews, 5 focus groups, and 2 cross-company workshops, we discuss possible scopes of agile methods within system development, the consequences this has on the role of requirements, and the challenges that arise from the interplay of requirements engineering and agile methods in large-scale system development. These relate in particular to communicating and managing knowledge about a) customer value and b) the system under development. We conclude that better alignment of a holistic requirements model with agile development practices promises rich gains in development speed, flexibility, and overall quality of software and systems.
Keywords: requirements engineering; large-scale agile; system engineering